Response strategies to maintain emotional resonant brand reputations when targeted by user-generated brand parodies - Maritha Pritchard; De la Rey Van der Waldt; David Pieter Conradie (Communicare)
Mostly satirising top-of-mind brands, user-generated parody accounts are a phenomenon mostly associated with Twitter. As an emerging trend in South Africa, parody accounts using cleverlywritten satire attract a large and loyal following as social media communities enjoy the shared pleasure of sharing funny content and the intense positive emotions felt when making fun of brands that they care about. Of particular concern is when audiences find parody accounts more honest, entertaining and authentic compared to the official social media brand account. Moreover, user-generated parody accounts often misappropriate brand identities, thereby not only confusing unsuspecting social media communities but also satirising brand meanings. Correspondingly, social media management teams are faced with a reputational risk or paracrisis, since the emotional resonance of brand reputations are being hijacked. Too often, official responses to parody accounts are knee-jerk responses to take back control, such as aggressive threats and litigation, easily escalating into angry viral social media backlashes. The purpose of the study was to establish suitable paracrisis response strategies for parodied brands to maintain emotionally resonant reputations. Using a synergistic approach to mixed methods in a triangulation design, this study collected and analysed data from a purposive and snowball sample of 207 social media experts. Findings suggested that humorous, tongue-in-cheek banter with user-generated parody accounts intended for harmless fun optimise emotionally resonant brand reputations in the age of parody.